A clean and efficient solar-aided de-NOx system in solar/fuel hybrid power plants. (5th February 2023) - Han, Yu; Sun, Yingying; Wu, Junjie
Graphical abstract: Highlights: A novel concept of power generation is proposed: solar-aided de-NOx . NOx removal is kept at the optimal range by parabolic trough solar energy. Solar energy is converted into furnace by air preheating process. High thermal, environmental and economic performances are achieved. Abstract: Based on the unique characteristics of parabolic trough solar energy and selective catalytic reduction de-NOx, a novel solar/fuel hybrid power generation system is proposed. In the system, solar energy is integrated with de-NOx for keeping the NOx removal temperature at the optimal range. The additional heat brought by solar energy is sent into furnace by the following air preheating process. Thermodynamic, environmental, and economic analyses of the novel system are conducted. Based on a typical reference unit, the proposed solar/fuel hybrid power generation system increases thermal efficiency by 1.24 % with 13.8 MWe of solar generated electric power, and achieves 25.3 % of solar-to-electricity efficiency. The solar-aided de-NOx system increases 8.5 % of NOx removal efficiency and reduces 19.8 g/s of NOx emission. For the economic performance, the proposed system brings 5.38 million USD of extra annual income with 0.052 USD/kWh of cost of solar generated electricity. Overall, the results of thermodynamic, environmental, and economic analyses indicate that solar-aided de-NOx is a promising way for clean and efficient electricity generation.